Biomass yield of rice (Oryza sativa) cultivars as affected by applied silicate in an Inceptisol - Arkaprava Roy; Siba Prasad Datta; Mandira Barman; Somnath Bhattacharyya; Mahesh Chand Meena; Debasis Golui; Vivek Kumar Trivedi; Ranabir Chakraborty (The Indian Journal of Agricultural Sciences, 2020)
West Bengal is the largest rice (Oryza sativa L) producing state of India. In spite of leading the world in rice production, India lags behind in terms of rice productivity. In view of limited information, a pot experiment was conducted at ICAR-IARI, New Delhi during kharif, 2018-19 to evaluate the response of important rice cultivars to applied silicate. The experiment was conducted with four rice cultivars (one indigenous aromatic and rest three HYVs) and three doses of sodium metasilicate (0, 250 and 500 mg/kg) using an alluvial Inceptisol collected from West Bengal. Results indicated that the grain and straw yield was increased up to 40.7 and 18.1%, respectively, due to application of silicate. Rice cultivars, on the basis of grain yield, can be arranged in the order: Khitish (20.8 g/ pot)> Satabdi (17.6 g/pot) > IR-36 (15.4 g/pot) >Badshabhog (3.72 g/pot). The highest and the lowest straw yield was recorded with Badshabhog (70.1 g/pot) and IR-36 (14.6 g/pot), respectively. Rice cultivars showed differential responses in terms of yield to applied silicate. It can be concluded that application of sodium metasilicate can be one of the effective options for enhancing rice yield in the alluvial Inceptisol of West Bengal.